Blockade of the T cell immunoglobulin and mucin domain protein 3 pathway exacerbates sepsis‐induced immune deviation and immunosuppression. (November 2014) - Zhao, Z.; Jiang, X.; Kang, C.; Xiao, Y.; Hou, C.; Yu, J.; Wang, R.; Xiao, H.; Zhou, T.; Wen, Z.; Feng, J.; Chen, G.; et al.
Summary Sepsis is a life‐threatening condition, but the pathophysiological basis and biomarkers for the monitoring of sepsis and as targets for therapy remain to be determined. We have shown previously that T cell immunoglobulin and mucin domain protein 3 (Tim‐3), a negative immune regulator, is involved in the physiopathology of sepsis, but the underlying mechanisms remain unclear. In the present study, we showed that Tim‐3 signalling modulated the response patterns of both macrophages and T helper cells in sepsis. Blockade of the Tim‐3 pathway exacerbated sepsis‐induced proinflammatory macrophage responses and lymphocyte apoptosis during the early phase of sepsis, and enhanced the shift to anti‐inflammatory responses for both macrophages and T helper cells during the late phase of sepsis. Tim‐3 signalling was found to regulate CD80 and CD86 expression on macrophages both in vivo and in vitro. Co‐culture of T cells with Tim‐3 knock‐down macrophages led to a biased T helper type 2 (Th2) response, partially explaining how Tim‐3 signalling shapes inflammation patterns in vivo. Further studies on this pathway might shed new light on the pathogenesis of sepsis and suggest new approaches for intervention.